Analysis of Community Economic Growth in the Middle of the Covid-19 Pandemic on the Agricultural Sector in the Regionsouth Sulawesi - Firmansyah (IECON: International Economics and Business Conference, 2023)
Economic growth is an indicator of successful development in an economy. The natural resources that have the most influence on the people's economy, especially in the South Sulawesiregion, are resources in the agricultural sector. Agriculture in South Sulawesi has many types and has itsown competitiveness in the eyes of the community, such as rice farmers, cloves, cocoa, and so on. In 2019, the economy in South Sulawesi increased quite high, reaching 5.46% according to Bank Indonesia data, but towards the end of the year and entering 2020, the economy in South Sulawesi experienced a decline which saw a sharp decline of up to 0.5% according to Bank Indonesia data . The decline in the economy was due to the Covid 19 pandemic which attacked various countries, especially Indonesia, including South Sulawesi. Covid 19 is a new virus that causes mysterious pneumonia in sufferers and this virus spreads quickly from one patient to another. The existence of the Covid 19 pandemic has caused several sectors in Indonesia to experience a downturn, one of which is the economic sector. The economic decline occurred due to the enactment of PSBB (Large-scale Social Restrictions) so that people were limited to carrying out their daily activities, especially buying and selling transactions. The type of research used in this research is the mix method, a combination of two types of research between qualitative and quantitative because the data taken comes from data that has been presented by Bank Indonesia, the Central Bureau of Statistics, and the Financial Services Authority, and data collection is carried out by using a questionnaire. (questionnaire).